Pregnancy management in patients with acromegaly - L. B. Markin; K. L. Shatylovych (Publishing House TRILIST, 2019)
Acromegaly is a rare, chronic, endocrine disorder, usually caused by hypersecretion of growth hormone (GH) for a prolonged period from a somatotroph adenoma. Hormonal evaluation becomes more complex in pregnant women due to physiological changes in the pituitary and target hormone levels, binding globulins, and placental hormones. Evaluation of pituitary functions in pregnant women is quite different from nonpregnant women because of physiological hormonal changes. Pregnancy in acromegaly continues to be an uncommon event and a challenge for clinicians despite the positive impact of current treatments on survival and quality of life. Diagnosis of acromegaly during pregnancy is difficult because of changes in GH and insulin like growth factor 1 (IGF 1) levels, GH production by placenta, and the inability of routine methods to distinguish the pituitary GH from placental GH. In the majority of patients with acromegaly pregnancy does not have an adverse effect on mother or fetus and pituitary mass does not increase in size. Tumor enlargement may theoretically occur if pre-existing therapies such as somatostatin analogues are discontinued with the onset of pregnancy. Acromegalic symptoms may improve during pregnancy, possibly from the increased estrogen production inhibiting hepatic IGF 1 production. Pregnancy course is mostly uneventful but the literature indicates an increased risk of gestational diabetes and gravid hypertension in women with non-controlled GH/IGF 1 hypersecretion before gestation. In case of tumor enlargement frequent monitoring is required, surgery can be considered in the second trimester. Dopamine agonists and somatostatin analogs can be used without any adverse consequences on mother or fetus. In pregnancy acromegaly medical therapy should be withheld and administered only for tumor growth and headache control during pregnancy. Breast feeding does not affect the course of acromegaly. Postpartum pituitary imaging demonstrates no increased tumor growth after pregnancy.